Directing Cardiomyogenic Differentiation and Transdifferentiation By Ectopic Gene Expression – Direct Transition Or Reprogramming Detour? - Andrée, Birgit; Zweigerdt, Robert (Current Gene Therapy, 2016)
Cardiovascular disorders and associated morbidities remain the leading cause of premature death worldwide. Since the regeneration of diseased hearts is very limited and the insufficient supply of donor organs persists, hopes rely on new therapies for heart repair. Reviving the proliferation of endogenous cardiomyocytes (CMs) or the administration of adult stem cells to the heart was of limited curative success to date. Thus, the administration of in vitro generated CMs is under investigation to replenish loss of functional heart muscle tissue. This requires a sustainable source of CMs. Induced pluripotent stem cells (iPSC) have raised hopes for developing autologous cell therapies. To serve for heart repair, efficient and safe iPSC differentiation protocols for CMs production are required. iPSC differentiation into CMs and even functional subtypes was indeed achieved in recent years, either by the ectopic expression of cardiac transcription factors or the supplementation of chemical pathway modulators. An alternative approach aims at the direct transdifferentiation of fibroblasts, which are present in the interstitial tissue of many organs, into functional lineage-specific cell types. As a result the formation of induced cardiomyocyte-like cells (iCMs) by the ectopic expression of specific transcription factors combinations has been demonstrated in vitro and in vivo. This is an important proof-of-concept that the intermediate state of iPSC induction is dispensable. However, most of the early experiments were conducted in mice and translation to more relevant large animal models and subsequently to the clinic are challenging. Progress, drawbacks, and perspectives in this field will be discussed.
Keywords: Induced pluripotent stem cells